Kirkendall Effect on the Nanoscale - Cserháti, C.; Langer, G.; Parditka, B.; Csik, A.; Iguchi, Y.; Czigány, Zs.; Erdélyi, Z. (Diffusion Fundamentals, 2017)
Kirkendall effect has been studied experimentally as well as theoretically for decades already. There are theoretical indications, that the Kirkendall effect must operate from the beginning of the diffusion process but there are practically no measurements on this short time and length scale. For that reason, diffusion on the nanometer scale was investigated experimentally in different binary systems in thin film geometry. We followed the diffusion process as well as the Kirkendall effect by different methods (TEM, SNMS and synchrotron X-ray waveguide technique). Investigations were performed in systems with complete solubility (Bi-Sb, Cu-Ni, Bi-Sb) as well as in systems forming intermetallic phase (Fe-Sb, Fe-Pd). It was found that with these methods the Kirkendall shift can be well followed on the nano-scale. In Fe-Sb system even the bifurcation of the Kirkendall plane was observed.